2013
DOI: 10.7600/jpfsm.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of homosynaptic depression during voluntary contraction and muscle fatigue with different test reflex size

Abstract: The Hoffmann (H-) reflex can be depressed when elicited repetitively at a frequency of ~1 Hz. This H-reflex depression is termed homosynaptic depression (HD) and is attributed to impaired neurotransmitter release from the presynaptic Ia terminal. In the present study, we systematically evaluated the extent to which HD in the soleus was modulated by the level of homonymous muscle contraction and the size of the test H-reflex. Changes in HD were also assessed while the target muscle was subjected to fatigue. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…These studies offered the best prediction of the behavior of PAD that might be expected in the present study. Similar to our findings, Takahashi and coauthors reported a significant reduction in homosynaptic PAD in fatigued muscle . Our study extends these findings to reveal an apparent restoration of PAD as exhaustion approaches.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These studies offered the best prediction of the behavior of PAD that might be expected in the present study. Similar to our findings, Takahashi and coauthors reported a significant reduction in homosynaptic PAD in fatigued muscle . Our study extends these findings to reveal an apparent restoration of PAD as exhaustion approaches.…”
Section: Discussionsupporting
confidence: 92%
“…Stein and coauthors highlighted the important differences in PAD that occur between rest and voluntary contraction, concluding that "Measurements at rest do not accurately represent the H-reflex during motor tasks". 6 In their work and in other reports, maintenance of a voluntary contraction yields a reduction in PAD and a concomitant increase in conditioned H-reflex amplitude, 9,25,31,32 similar to what we observed at F1 and F2. None of these reports examined fatigue to exhaustion.…”
supporting
confidence: 90%
See 3 more Smart Citations